Оperation «labyrinth» in surgical treatment of combined mitral-аоrtic failures - V. V. Popov; А. А. Bolshak; V. V. Lazoryshynets (Клінічна хірургія)
Objective. Studying possibilities concerning the proposed procedure of intraoperative restoration of the sinus rhythm in surgical treatment of combined mitral-аоrtic failures.